Board Diversity and Dividend Payout Ratio: Evidence from Family Firms in Indonesia - Setiawan, Rahmat; Aslam, Annisa Paramaswary (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2018)
This study investigates the impact of Board of Commissioners (BoC) diversity on dividend payments in the listed family firms in Indonesia. This study uses diversity for gender, nationality and tenure to describe the board of commissioners diversity. Using a data set of listed family firms in Indonesia Stock Exchange over the period 2012-2016, we find evidence indicating that board gender diversity is positively related to dividend payments. Secondly, we find evidence that board tenure diversity is positively related to dividend payments. However, the board nationality diversity does not remain significant on dividend payments.